SYSTEMATIC LITERATURE REVIEW: STRATEGI PEMBELAJARAN ILMU SHARAF BERDASARKAN TEORI PEMBELAJARAN TERPADU - Kamal Ramdani; Choiruddin; Moh. Ikhsani (Program Studi Pendidikan Bahasa Arab, 2024)
This study aims to find out the Arabic language learning strategy for Ilm Sharaf based on the Integrated Learning theory. Students are required to be able to master Arabic, especially Ilm Sharaf. However, the existing learning strategies are generally not ideal. Learning still relies on conventional methods so that interaction with students is very minimal. The availability of quality teachers, curriculum, learning resources and learning strategies is still very limited. This study used a qualitative method by means of Systematic Literature Review. Data collection techniques focus on identifying data sources, determining inclusion and exclusion criteria, searching and selecting, and extracting data. The results of the study showed that there were six Arabic language learning strategies based on the Integrated Learning theory, namely: integration of subjects, relationships between concepts, application in real contexts, development of critical thinking skills, teacher collaboration, and development of lifelong skills. These results are expected to be developed in learning Arabic Ilm Sharaf practically and systematically.